2016
DOI: 10.1016/j.bbabio.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The strontium inorganic mutant of the water oxidizing center (CaMn4O5) of PSII improves WOC efficiency but slows electron flux through the terminal acceptors

Abstract: Herein we extend prior studies of biosynthetic strontium replacement of calcium in PSII-WOC core particles to characterize whole cells. Previous studies of Thermosynechococcus elongatus found a lower rate of light-saturated O2 from isolated PSII-WOC(Sr) cores and 5-8× slower rate of oxygen release. We find similar properties in whole cells, and show it is due to a 20% larger Arrhenius activation barrier for O2 evolution. Cellular adaptation to the sluggish PSII-WOC(Sr) cycle occurs in which flux through the QA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 71 publications
2
24
0
Order By: Relevance
“…For example, Boussac et al observed that in both Ca and Sr PSII, the high-spin form of the S 2 state is capable of advancing to S 3 at low temperature (198 K), and they suggested this to be an experimental demonstration that the low-spin S 2 state advances to S 3 via the high-spin S 2 state without detectable intermediates. Gates et al similarly concluded that the S = 5 / 2 form of the S 2 state, the form stabilized by strontium substitution, is the active form in the catalytic cycle relative to the low-spin S = 1 / 2 form.…”
Section: The S2–s3 Transitionmentioning
confidence: 99%
“…For example, Boussac et al observed that in both Ca and Sr PSII, the high-spin form of the S 2 state is capable of advancing to S 3 at low temperature (198 K), and they suggested this to be an experimental demonstration that the low-spin S 2 state advances to S 3 via the high-spin S 2 state without detectable intermediates. Gates et al similarly concluded that the S = 5 / 2 form of the S 2 state, the form stabilized by strontium substitution, is the active form in the catalytic cycle relative to the low-spin S = 1 / 2 form.…”
Section: The S2–s3 Transitionmentioning
confidence: 99%
“…These 8 parameters are the same for all temperatures, assuming linear Arrhenius plots in the temperature range from 0 to 30°C. The linear Arrhenius plot is predicted by standard electron-transfer as well as transition-state theory and largely has been experimentally confirmed for the reactions in the oxygen-evolving complex of PSII (Klauss et al, 2012; Bao and Burnap, 2015; Klauss et al, 2015; Gates et al, 2016). Using this rationale, instead of 7 × 9 = 63 adjustable parameter for the set of 7 DF decays measured at different temperatures, the overall number of parameters was reduced to 8 + 5 × 7 = 43 free parameters (Zaharieva et al, 2013).…”
Section: Resultsmentioning
confidence: 54%
“…As no change in miss parameters was found in the latter sample types, we attribute this phenomenon (of increased O 2 signals) to a sedimentation of the samples onto the membrane surface that covers Pt‐electrode during relatively long FIOPs measurements. Precisely, the same settling phenomenon is seen with whole cells of algae (Gates et al ).…”
Section: Resultsmentioning
confidence: 55%
“…S1). Because DMBQ, in contrast to PPBQ/FeCy, does not provide significant artifacts in FIOPs experiments (Ananyev et al , Gates et al ), DMBQ was employed throughout this study.…”
Section: Resultsmentioning
confidence: 99%